Genomic insights about the effect of sodium-glucose cotransporter 2 inhibitors: a systematic review - Pavitraa Saravana Kumar; Yogapriya Chidambaram; G. Shree Devi; Vettriselvi Venkatesan; Ramesh Sankaran; Nagendra Boopathy Senguttuvan; Thanikachalam Sadagopan; Dorairaj Prabhakaran (Frontiers in Genetics)
IntroductionHeart failure (HF) is a complex clinical syndrome with high morbidity and mortality, significantly burdening healthcare systems worldwide. Despite advances in therapy, effective treatment options remain limited. Sodium-glucose cotransporter 2 (SGLT2) inhibitors, initially developed for diabetes management, have demonstrated cardiovascular benefits, including reductions in HF hospitalizations and mortality. This systematic review examines the genomic effects of SGLT2 inhibitors in HF patients, focusing on gene expression, inflammatory biomarkers, and potential personalized treatment pathways.MethodsA systematic literature search of various databases was conducted up to November 2024, following PRISMA guidelines. Studies were included if they explored the genomic or molecular impacts of SGLT2 inhibitors in HF. Data extraction and analysis focused on gene expression changes, circulating biomarkers, and potential genomic mechanisms.ResultsOf the 258 identified studies, three met the inclusion criteria. Key findings include: a) SGLT2 inhibitors downregulate pro-inflammatory genes in adipose tissue, reducing immune cell infiltration and ferroptosis; b) Genetic evidence highlights CXCL10 as a mediator of anti-inflammatory effects, with its inhibition linked to reduced HF risk; c) LRRTM2, a protein associated with synaptic formation, emerged as a critical mediator, with genetic links to reduced HF risk via SGLT2 inhibition.DiscussionThis review underscores the genomic mechanisms through which SGLT2 inhibitors provide cardiovascular benefits. Key insights into gene expression modulation and protein interactions reveal pathways for personalized HF treatment. While findings are promising, further large-scale studies are needed to validate these mechanisms and their clinical implications.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024614674.